ELSI is Our Next Battlefield. Issue 1 (2nd January 2021) - Mikami, Koichi; Ema, Arisa; Minari, Jusaku; Yoshizawa, Go
Abstract: ELSI refers to "ethical, legal, and social issues/implications" of science and technology (S&T). The term has been gaining currency in Japan over the last 15 years in the context of its national S&T policy. In this essay, we argue that ELSI will become a pivotal concept characterizing the relationship between S&T and social sciences and humanities (SSH) in the country, due particularly to the first-ever amendment to the S&T Basic Law scheduled in April 2021. And because ELSI is recognized as an area of work that STS scholarship should play a major part in, how the local STS community is going to respond to the change this leads to will have a decisive impact on the way in which the relationship becomes characterized. The government's persistent use of the term despite the criticism it has received reveals an assumption underpinning its S&T policy about the way in which the work of SSH contributes to S&T and helps to foster innovation. It is therefore important for the community to challenge such an assumption and reframe the role of SSH, if it believes in the societal value of its scholarship and the critical sensibilities that its research offers.